An Empirical Re-examination of Exchange Rate-Trade Balance Nexus in Nigeria (2013)
The Nigerian exchange rate-trade balance nexus was re-examined. The long run relationship between these variables was explored using the Gregory-Hansen cointegration approach on a data sample between 1980:Q1 and 2010:Q4. Prior to this, three efficient integration tests that can overcome potentially severe finite sample power and size problems suffered by the standard methods were tactfully pursued for robustness. The short run impact analysis was done in the error correction framework. The analyses showed that exchange rate depreciation led to trade balance deterioration in both the short run and the long run. Thus, this study could not find support for J-curve in Nigeria. Some suggestions on the way forward were put forth.